Outcome of children with neuromuscular disease admitted to paediatric intensive care. Issue 2 (21st January 2004) - Yates, K; Festa, M; Gillis, J; Waters, K; North, K
Abstract : Aims: To determine the outcome of children with neuromuscular disease (NMD) following admission to a tertiary referral paediatric intensive care (PICU). Methods: All children with chronic NMD whose first PICU admission was between July 1986 and June 2001 were followed up from their first PICU admission to time of study. The outcomes recorded were death in or outside of PICU, duration of PICU admission, artificial ventilation during admission and following discharge from PICU, and readmission to PICU. Results: Over 15 years, 28 children were admitted on 69 occasions. Sixteen (57%) children had more than one admission. The median duration of PICU admission was 4 days (range 0.5–42). Twenty three per cent of unplanned admissions resulted in the commencement of respiratory support that was continued after discharge from the PICU. Severity of functional impairment was not associated with longer duration of stay or higher PRISM scores. Ten children (36%) died, with four (14%) deaths in the PICU. A higher proportion of children with severe limitation of function were among children that died compared to survivors. Conclusion: Most children with NMD admitted to the PICU recover and are discharged without the need for prolonged invasive ventilation. However, in this group of children, the use of non-invasive home based ventilation is common and they are likely to require further PICU admission.